Promoting scientific research at universities in Vietnam - Cao, Thanh Phước; Phan, Quốc Cường; Le, Văn Cường (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
Scientific research plays an important role in contributing to the improvement of the training quality and creating high-quality human resources for meeting social needs. The university is a place for training and fostering human resources at undergraduate and graduate levels, and is also a scientific research facility. The university’s scientific research is obviously part of the process of improving the quality of education and training. This article aims to analyze the advantages and disadvantages of the practical scientific research at several universities in Vietnam nowadays, and thus determining the causes and proposing several solutions for promoting activities as such at universities in Vietnam in general.